An improved particle method for simulating Fluid-Structure Interactions: The multi-resolution SPH-VCPM approach - Ng K.C.; Alexiadis A.; Ng Y.L. (Elsevier Ltd, 2023)
Computational efficiency; Fluid structure interaction; Hydraulics; Fluid structure interaction; Fluid-structure interaction; Free surfaces; Lattice spring model; Multi-resolution; Particle methods; Smoothed particle hydrodynamic; Smoothed particle hydrodynamics; Volume compensated particle method; Hydrodynamics; computational fluid dynamics; fluid-structure interaction; free surface flow; hydrodynamics; model; spatial resolution